Toward an evaluation framework for Education 5.0 in institutions of higher learning in Zimbabwe - Mupaikwa, Elisha (Frontiers in Education, 2025)
Education 5.0 was introduced in 2019 to address Zimbabwe's National Development Agenda. However, to date, no study has evaluated Education 5.0, and no framework has been developed to perform this evaluation in Zimbabwe's institutions of higher learning. This study aims to develop a framework to evaluate Education 5.0 in Zimbabwe's institutions of higher learning. This study adopted the systematic literature review approach on journal articles from academic databases such as EmeraldInsight, Google Scholar, PubMed, ERIC and JSTOR. A total of 123 articles were downloaded from these 40 were considered for the review. The major findings of the study were that the success of Education 5.0 was influenced by the availability of digital infrastructure and associated digital literacies. The study further revealed that innovation competencies influenced innovative strategies implemented in institutions of higher learning and that each of the five major variables was measured by a set of attributes. Challenges that confronted educational institutions in implementing Education 5.0 included resistance to change, lack of funding, lack of physical and digital infrastructure, resistance by academic staff members and students and their negative perceptions toward Education 5.0.